37 Mechanical And Structural Properties Of Stem Cell-based Tissue Engineered Constructs (tec) Cultured With Collagen Sheets. (5th September 2014) - Ikeya, Motoshi; Oya, Kei; Suzuki, Daisuke; Ogura, Takayuki; Koyama, Yoichi; Sugita, Norihiko; Nakamura, Norimasa; Fujie, Hiromichi
Abstract : Introduction: Stem cell-based tissue engineered construct (TEC) biosynthesized from synovium-derived mesenchymal stem cells (MSCs) has a great potential for repairing and regenerating ligaments and tendons1. However, the mechanical and structural properties of the TEC were insufficient for clinical applications. A candidate solution to the problem is to promote the generation of the extracellularmatrix inthe TECusing a special culture withcollagen sheets (CS). Previous studies indicated thattheCS has an abilitytorepair fibrous tissuesin vivo4. In addition, the biosynthesis of extracellular matrix is promoted by cell culturing in the existence of collagen. 2 In the present study, TECwas culturedwiththe CS, then the tensile properties of TEC/CS composite were assessed. Materials and Methods: The CS wasproduced from porcine corium-derived collagen-rich tissues, through homogenization, centrifugal separation, filtering, and dehydration. It should be noted that the sheets are porous and chemical agent-free materials with collagen density between 20 and 30%. MSCswere obtained from the synovial membranes of human knee joint by means of collagenase treatment. After 5 time passages, the cells were plated at the density of 4.0 × 105 cells/cm2 on the CS (TEC/CS), and ontissue culturepolystyrenedishes (TEC). The cells were culturedto produce construct of extracellular matrix for 1, 4, and 8 weeks in the DMEM1. In addition, the CS was also immersed in the same medium without cells for 4 weeks (CS). TEC/CS, TEC, and CS weresubjected to tensiletest at arate of 0.05 mm/s in a PBS solution at 37 °C using acustom-made micro tensile tester. 3 Morphological observations of the tissues were carried out using a scanning electron microscopic (SEM)and an optical microscope with hematoxylin-eosin (HE) staining. Results and discussion: The tangent modulus and tensile strengthofTEC/CSgroupwere continuously increased. In addition, those of TEC/CS after 8-week cultivation were significantly higher than those of CS. The load at failure of TEC/CS group was significantly lower than those of CS and TEC groups at 1 week. However, it was increased subsequently and reached to 0.18 ± 0.05 N at 8 weeks, with significant differences vs. CS (0.07 ± 0.02 N) and TEC (0.12 ± 0.05 N) groups. References: 1 Ando W, et al . Biomaterials. 2007;28:5462–5470 2 Gentleman E, et al . Biomaterials. 2003;24: 3805–3813 3 Nagai H, et al . Japanese Jounal of Clinical Biomechanics . 2006;27:89–93 [in Japanese] 4 Suzuki D, et al . abstract. Jounal of Japanese Clinical Biomechanics. 39